KAJIAN TINGKAH LAKU MONYET EKOR PANJANG (Macaca Fascicularis) OBES DALAM KANDANG INDIVIDU - Pijoh, Deyv; Astuti, Dewi Apri; Mansjoer, Sri Supraptini; Sajuthi, Dondin; Suparto, Irma Herawati (ZOOTEC, 2020)
STUDY ON BEHAVIOUR OF THE LONG TAIL MONKEY (Macaca fascicularis) OBESE IN INDIVIDUAL CAGE. This study was designed to obtain information of development behaviour the obesity of long-tailed monkey (Macaca fascicularis) fed with high energy obes diet. The need of obese monkeys highly to model byomedis obesity. Obesity is now a universal problem that needs to be explored and studied. Therefore, the objective of this research was to develop obese adult male monkeys with high energy food for 12 months and monitoring their behaviour. Fifteen adult male monkeys 6-8 years old with the weight of between 4-5 kg were divided equally into three groups. The first group was body weight average 4.50 kg, the second group was body weight average 5.00 kg; and the third group was body weight average 4.75 kg. The results showed that body weight gave a significant effect (P <0.01) on daily behaviour and also gave a significant effect (P<0.01) on fed behaviour frequently,drink behaviour, agonistic behaviour, grooming behaviour, and locomotion behaviour .Keywords: Behaviour frequently, Long-tailed monkey (Macaca fascicularis), Obesity)